In vitro growth of bovine oocytes in oocyte-cumulus cell complexes and the effect of follicle stimulating hormone on the growth of oocytes - Mihoko FUSHII; Rie YAMADA; Takashi MIYANO (The Society for Reproduction and Development, 2020)
Several successful in vitro culture experiments have used oocyte-cumulus cell-mural granulosa cell complexes (OCGCs) from early antral follicles (0.5-0.7 mm) for the growth of bovine oocytes. However, in studies related to in vitro oocyte maturation and in vitro embryo production, oocyte-cumulus cell complexes (OCCs) that have no mural granulosa cells have been widely used instead of OCGCs. The purpose of this study was to determine whether cumulus cells alone support oocyte growth. First, OCCs and OCGCs were cultured in vitro for 14 days to compare the integrity of the complexes as well as antrum formation. After 14 days, the diameter and meiotic competence of oocytes in OCCs and OCGCs were examined. Oocytes in OCCs grew fully and acquired meiotic competence similar to OCGCs, whereas antrum formation occurred later in OCCs as compared to OCGCs. Subsequently, the effects of follicle stimulating hormone (FSH) on in vitro growth of OCCs were examined for 14 days. When FSH was added to the culture medium, OCCs formed antrum-like structures one day earlier than those cultured without FSH. Oocytes cultured with 1 mIU/ml FSH grew fully and acquired meiotic competence. In contrast, when oocytes were cultured in media containing high concentrations of FSH, some of the OCCs collapsed and the number of degenerated oocytes increased. In conclusion, bovine oocytes in OCCs grow and acquire meiotic competence similar to OCGCs and, 1 mIU/ml FSH supports the development of OCCs and oocyte growth as observed in our culture system.